Isotopic signatures of Frenulata from cold seeps in the Gulf of Cadiz - Carramaschi, Guilherme Leite (2018)
Siboglinids are tube-dwelling annelids that are important members of deep-sea chemosynthetic communities, which include hydrothermal vents, cold seeps, whale-falls and reduced sediments. As adults, they lack a functional digestive system and rely on microbial endosymbionts for their energetic needs. Currently most researchers recognize four main lineages within Siboglinidae, Frenulata, Vestimentifera, Sclerolinum and Osedax, of which Frenulata is the most understudied. The discovery of chemosynthetic-based communities dominated by frenulates in several mud volcanoes in the Gulf of Cadiz, and the possibility to explore these habitats through several research programmes has been an excellent opportunity to extend our knowledge on these fascinating tubeworms. As other chemosymbiotic animals, frenulates have depleted values of δ13C that result from the metabolic pathways of their associated bacteria. In this study, stable isotope signatures were used to determine (1) the energy source (methane or sulphur) of the endosymbionts of different species of frenulates, (2) the occurrence of resource partitioning between species inhabiting the same site and (3) differences in the energy sources of the same species inhabiting different sites. Additionally, the effect of different sample preservation methodologies (frozen, ethanol, and formaldehyde) in the isotopic signatures was also compared. The δ13C values of both species from Porto mud volcano indicate that these species may host methanotrophic symbionts and that they are able to exploit different microhabitats within the same seep site. The carbon isotopic signatures were more (Spirobrachia tripeira and Lamellisabella denticulata) or less (Siboglinum cf. poseidoni) depleted than expected suggesting that dual symbiosis may be more prevalent than previously though in frenulates. It is hypothesized that dual symbioses allow frenulates to survive in the spatially and temporally variable chemical environment of mud volcanoes. The effects of the preservation method on δ13C and δ15N values is in agreement with previous studies and suggest that frenulate samples preserved chemically can be used in trophic ecology studies. However results obtained with samples including the chitinous tube of the animals should be interpreted with caution.